2018
DOI: 10.1002/capr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy for depression from the point of view of economically disadvantaged individuals in Chile and Colombia

Abstract: Background This article presents a qualitative study, conducted in Chile and Colombia, on mental health care access and experiences with psychotherapy from the perspectives of economically disadvantaged clients. Current epidemiological data show it is important to conduct psychological interventions to address depression in poor populations, given the high prevalence of this disorder in these groups. However, despite efforts made in both countries at the health care policy level, the impact of the available ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
4
Order By: Relevance
“…This was achieved through a reconceptualisation of the aetiology of their problems, which in many cases involves the convergence of factors belonging to multiple areas [50].…”
Section: Therapy Processes and How They Impact On Outcomes Therapy Prmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved through a reconceptualisation of the aetiology of their problems, which in many cases involves the convergence of factors belonging to multiple areas [50].…”
Section: Therapy Processes and How They Impact On Outcomes Therapy Prmentioning
confidence: 99%
“…Specifically in MBCT, the practice of the "body scan" was reported to trigger flashbacks or severe anxiety for some participants with a history of abuse or trauma [27]. In a study of public psychotherapy for economically disadvantaged Chileans and Colombians, it was found that therapy could sometimes feel unfocused and unclear [50]. Two studies, one with Hmong people and one with older white Americans found that therapy was felt to ignore spirituality [49,57].…”
Section: Therapy Processes: What's Unhelpfulmentioning
confidence: 99%
“…Dentro de los factores de riesgo reportados en este estudio se encuentran mayor edad, insatisfacción con la carrera y bajo nivel económico propio y de los padres. En este sentido, las variables socioeconómicas anteriormente mencionadas resultan relevantes para comprender las diferencias en la sintomatología depresiva y el bienestar psicológico en estudiantes universitarios 7,9,10 . Un metaanálisis realizado en el año 2016 muestra cifras similares en estudiantes universitarios del área de la salud 11 .…”
unclassified
“…Similarly, the Black, Asian and minority ethnic (BAME) label amalgamates a number of distinct cultures and ethnicities with heterogeneous experiences. Much of the • Institutional challenges, such as time/ length of session [32,49] • Inexperienced or unhelpful staff [50] • Lack of provision of home treatment [50] • Lack of service coordination [34] • Limited treatment options [147] • Long waiting lists and availability of treatment [44,147] • Lack of adequate discharge planning [56] • The use of specialist services as the 'default' [57] • Perceived or actual availability of resources [57] • Inappropriate or limited booking systems [66] • Appointments scheduled during working hours [38] • Perceived difficulties in administering treatment [141] • Diversity of treatment options (e.g. outreach, home-based care, help over the phone, street clinics) [147] • Collaborative agency approach [32] Perceived or real discrimination (from staff, family or the community)…”
Section: Strengths and Limitationsmentioning
confidence: 99%